CSF β-amyloid and white matter damage: a new perspective on Alzheimer's disease. Issue 4 (20th October 2017) - Pietroboni, Anna M; Scarioni, Marta; Carandini, Tiziana; Basilico, Paola; Cadioli, Marcello; Giulietti, Giovanni; Arighi, Andrea; Caprioli, Michela; Serra, Laura; Sina, Clara; Fenoglio, Chiara; Ghezzi, Laura; et al.
Abstract : Objective: To assess the connection between amyloid pathology and white matter (WM) macrostructural and microstructural damage in demented patients compared with controls. Methods: Eighty-five participants were recruited: 65 with newly diagnosed Alzheimer's disease (AD), non-AD dementia or mild cognitive impairment and 20 age-matched and sex-matched healthy controls. β-amyloid1-42 (Aβ) levels were determined in cerebrospinal fluid (CSF) samples from all patients and five controls. Among patients, 42 had pathological CSF Aβ levels (Aβ(+)), while 23 had normal CSF Aβ levels (Aβ(−)). All participants underwent neurological examination, neuropsychological testing and brain MRI. We used T2-weighted scans to quantify WM lesion loads (LLs) and diffusion-weighted images to assess their microstructural substrate. Non-parametric statistical tests were used for between-group comparisons and multiple regression analyses. Results: We found an increased WM-LL in Aβ(+) compared with both, healthy controls (p=0.003) and Aβ(−) patients (p=0.02). Interestingly, CSF Aβ concentration was the best predictor of patients' WM-LL (r=−0.30, p<0.05) when using age as a covariate. Lesion apparent diffusion coefficient value was higher in all patients than in controls (p=0.0001) and correlated with WM-LL (r=0.41, p=0.001). In Aβ(+), WM-LL correlated with WM microstructural damage in the left peritrigonal WM (p<0.0001). Conclusions: WM damage is crucial in AD pathogenesis. The correlation between CSF Aβ levels and WM-LL suggests a direct link between amyloid pathology and WM macrostructural and microstructural damage.